ANALYSIS OF FACTORS RELATED TO INTENTION-TO-USE TELEMEDICINE SERVICES (TELECONSULTATION) IN JABODETABEK RESIDENTS DURING THE COVID-19 PANDEMIC IN 2021 - Salsabila, Isna Mutiara; Sari, Kurnia (Journal of Indonesian Health Policy and Administration, 2022)
The emergence of COVID-19 pandemic has made it difficult for people to access health services. According to JKN statistics, FKTP visits was decreased from 337.69 million (2019) to 193.03 (2021). Teleconsultation, a type of telemedicine, could be the right solution so that people can still access the health services they need and protect themselves from the spread of COVID-19. There was an increase in the use of several teleconsultation applications in Indonesia during pandemic, from 4 million to more than 15 million people. However, this rate is only 7.63% of the internet users and 5.6% of the total population of Indonesia, so increasing access to health services through telemedicine is still challenging to achieve. Therefore, this study aims to determine the description and factors related to the intention to use health teleconsultation services during COVID-19 pandemic among Jabodetabek residents aged 19-49. This quantitative study used a cross-sectional design and PLS-SEM data analysis method. The results showed a significant relationship between social influence, perceived usefulness, trust in providers, and trust in the internet on the intention to use teleconsultation services. Intention-to-use was also significantly related to the use of teleconsultation services. In addition, a significant relationship was found between perceived need with trust in the provider, and perceived health risk and perceived ease of use with perceived usefulness.